ANALISIS KEPATUHAN IMPLEMENTASI UU RI NOMOR 6 TAHUN 2014 TENTANG DESA PASAL 71 - 75 SERTA PERATURAN TURUNANNYA DI DESA SIMPANG EMPAT - Eko Febri Lusiono; Suharman Suharman (Politeknik Negeri Batam, 2017)
The purpose of this research is to analyze compliance of the village government implementing UU RI nomor 6 tahun 2014 about the village, especially on paragraph 71-75 and the derivatives regulation governing about village financial management cycle. The research method used is descriptive qualitative method. To obtain the data, writers used data collection techniques include gradual interview and documentation techniques. Based on data obtained from various sources concluded that there are three indicators to measure the level of compliance of the village administration in the village financial management cycle. Three indicators are visible from the village knowledge about the UU RI nomor 6 tahun 2014 and derivatives regulation on the financial management of the village, the village financial management cycle, and adherence to the village financial management principles. Guidance and supervision by the central and local governments is indispensable for the village government in managing the finances of the village. Implementation of the law is a form of village government compliance towards good governance.